Sand Production Prediction Model for Tight Sandstone Oil Reservoirs - Zhan-dong Li; Hong Pang; Zhong Li; Hai-xiang Zhang; Dian-ju Wang; Ji Li (Geofluids)
Tight oil is an important unconventional resource, and sand production is an inevitable challenge during the field development. In this paper, based on data from the Daqing oilfield in Songliao Basin, the sand production of the tight sandstone oil reservoir is studied from the perspective of seepage and in situ stress distribution. Based on the combination of the formation fluid seepage law and the stress distribution around the well, a sand production prediction model is proposed to quantitatively estimate the sand production rate. The sand production prediction model is built based on the derivation of the sand production rate, which is well validated against the field data in the Daqing field with a relative error of 4.38%.The following conclusions are drawn: (1) after the critical pressure difference is exceeded, the sand production rate is smaller with a higher flowing bottom-hole pressure; (2) a smaller sand production radius makes the formation more unstable and causes a more severe sand production; and (3) various sand production rates exhibit due to different permeabilities. A larger permeability results in a higher sand production rate. The findings of this study can help for sand production prediction in the tight sandstone oil reservoir.